IoT-Enabled Dual Authentication System Using RFID and Passcode for College Dormitories - Deeva Haren Pannirselvam; Mohd Hakimi Bin Zohari (Progress in Engineering Application and Technology, 2025)
This project developed an IoT-enabled dual authentication system using RFID and passcodes for university dormitory security. Conventional access control methods like mechanical locks, standalone RFID cards, or passwords alone are insufficient due to vulnerabilities such as duplicated keys, cloned cards, and compromised passwords. The proposed system integrates RFID and passcode validation using an ESP32 microcontroller, providing two-step verification for authorized residents. The system includes IoT functionality through Firebase Realtime Database to log all access attempts and failed authentications, enabling real-time monitoring. Hardware components include RFID readers, keypads, SG90 servo motors, LCD display, and buzzer for user feedback. When both authentication factors are verified, the system unlocks doors and automatically re-locks after a set period. Administrative override using master RFID card and passcode is available for lockout recovery. Testing demonstrated reliable user authentication, unauthorized entry prevention, and effective event recording. The prototype showed good usability, response speed, durability, and feedback mechanisms. The dual verification approach significantly enhances security over traditional methods and offers a scalable solution for dormitory access control. By combining secure hardware with real-time cloud integration, the system improves student safety and provides administrators with efficient monitoring tools.